Exitianus obscurinervis (Hemiptera: Cicadellidae), a New Experimental Vector of Spiroplasma kunkelii - Carloni, Edgardo José; Virla, Eduardo Gabriel; Paradell, Susana Liria; Carpane, Pablo D.; Nome Docampo, Claudia; Laguna, Irma Graciela; Gimenez, Maria De La Paz (Oxford University Press, 2025)
“Corn stunt” caused by the mollicute Spiroplasma kunkelii (Whitcomb) is potentially one of the most severe diseases affecting the corn (Zea mays L.) crop in the Americas, and the leafhopper Dalbulus maidis (DeLong & Wolcott) is considered its most important vector. However, other insects seen quite frequently in corn crops might well be its vectors in Argentina. To identify any leafhoppers species other than D. maidis that can transmit S. kunkelii, transmission assays were conducted, using individuals of Exitianus obscurinervis (Stål) collected in field and reared under controlled conditions. S. kunkelii was transmitted to corn plants by E. obscurinervis. The pathogen was transmitted to seven of the 11 plants, which showed characteristic corn stunt symptoms, and the presence of the pathogen was confirmed by DAS-ELISA. The presence of S. kunkelii in the E. obscurinervis individuals used in transmission experiments was confirmed by polymerase chain reaction and electron microscopy. The current study shows the existence of a new experimental vector of S. kunkelii, the leafhopper E. obscurinervis, which acquired spiroplasmas from infected plants and inoculated it to healthy plants.